INTRANSIGENCE AND SELF-IDENTITY IN NAVARIA’S NEW CUSTOM - M. Ramalingam; Dr. N. Ranjithkumar; Dr. S. Ramanathan (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The shot story New Custom crystal clearly expose the prevailing caste system in ourcountry. Though everything may change, the caste system in India will never change. Ever if our India become a developed country, it is hard for our people to get away from this ridiculous practice of casteism. Ajay Navaria has beautifully brings about that no one can erase casteism from the mind of people, such as the people of Rajgarh in the story New Custom. Action that are taken to prevent casteism remains only a printed text , it doesnt come into practice and it won’t unless the antibiotic enters in, which is education. Well educated and scholarly men will never think of it.thats how the protagonist of this short story be like. He has been portrayed as a pure, and good hearted soul .it is true that unless we change the belief, we could not change ones character. The belief of a person can be changed only by Education. Education is the ligh ,which eliminate the darkness which abound the society.